Perlindungan Hukum Terhadap Anak Sebagai Korban Tindak Pidana Pencabulan - Sirait, Ingrid Debora; Adam, Sherly; Sopacua, Margie Gladies (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: Cases of criminal acts of sexual abuse against children, especially those handled by the Central Maluku Police, from 2021 to 2023, there were 9 (nine) cases of criminal acts of sexual abuse.Purpose of the Research: This research aims to enable investigators to know the child's personality and make it easier to carry out examinations. At the Central Maluku Police, since the start of the investigation process, children as victims of criminal acts of sexual abuse have not received rehabilitation either physically, psychologically or socially from P2TP2A Central Maluku.Methods of the Research: This type of research is normative juridical research using several approaches including the statutory approach, conceptual approach and case approach, using primary, secondary and tertiary legal material sources. Collection procedures The legal material used in this writing is a literature study (Library Research), which is descriptive qualitative in nature. In carrying out the study, this research also conducted interviews with police officers at the Women and Children Protection Unit at the Central Maluku Police.Result of the Research: The legal protection efforts carried out by the Central Maluku Police against children as victims of criminal acts of sexual abuse include the following: Confidentiality of the victim's identity; rehabilitation efforts; victims are entitled to legal aid and other assistance: providing protection and assistance during the prosecution investigation process until the trial process; obtaining information about the progress of the trial and always monitoring the development of the situation from the area where the victim lives; taking steps to cooperate with police ranks from various regions and from the Maluku Police; providing motivation and providing the best solution for the lives of children; and establishing communication and providing supervision for victims of criminal acts of sexual abuse who are still undergoing the process or who have completed the process. The obstacles faced by the Central Maluku Police in providing legal protection to children as victims of criminal acts of sexual abuse include law enforcement factors; community factors; facilities or facilities factors; cultural factors; and legal factors.